Phylogeography of Camellia taliensis (Theaceae) inferred from chloroplast and nuclear DNA: insights into evolutionary history and conservation - Liu, Yang (BioMed Central, 2012)
BACKGROUND: As one of the most important but seriously endangered wild relatives of the cultivated tea, Camellia taliensis harbors valuable gene resources for tea tree improvement in the future. The knowledge of genetic variation and population structure may provide insights into evolutionary history and germplasm conservation of the species. RESULTS: Here, we sampled 21 natural populations from the species' range in China and performed the phylogeography of C. taliensis by using the nuclear PAL gene fragment and chloroplast rpl32-trnL intergenic spacer. Levels of haplotype diversity and nucleotide diversity detected at rpl32-trnL (h = 0.841; π = 0.00314) were almost as high as at PAL (h = 0.836; π = 0.00417). Significant chloroplast DNA population subdivision was detected (G(ST) = 0.988; N(ST) = 0.989), suggesting fairly high genetic differentiation and low levels of recurrent gene flow through seeds among populations. Nested clade phylogeographic analysis of chlorotypes suggests that population genetic structure in C. taliensis has been affected by habitat fragmentation in the past. However, the detection of a moderate nrDNA population subdivision (G(ST) = 0.222; N(ST) = 0.301) provided the evidence of efficient pollen-mediated gene flow among populations and significant phylogeographical structure (N(ST) > G(ST); P < 0.01). The analysis of PAL haplotypes indicates that phylogeographical pattern of nrDNA haplotypes might be caused by restricted gene flow with isolation by distance, which was also supported by Mantel’s test of nrDNA haplotypes (r = 0.234, P < 0.001). We found that chlorotype C1 was fixed in seven populations of Lancang River Region, implying that the Lancang River might have provided a corridor for the long-distance dispersal of the species. CONCLUSIONS: We found that C. taliensis showed fairly high genetic differentiation resulting from restricted gene flow and habitat fragmentation. This phylogeographical study gives us deep insights into population structure of the species and conservation strategies for germplasm sampling and developing in situ conservation of natural populations.